Assessment of coronary artery stents by 16 slice computed tomography. Issue 1 (21st April 2005) - Gilard, M; Cornily, J C; Pennec, P Y; Le Gal, G; Nonent, M; Mansourati, J; Blanc, J J; Boschat, J
Abstract : Objective: To analyse coronary stents with multislice spiral computed tomography (MSCT) in comparison with coronary angiography. Patients and methods: 310 patients referred for conventional coronary angiography underwent MSCT on the next day (16 × 0.75 mm cross section, 420 ms rotation, 110 ml contrast agent intravenously at 4 ml/s). Two independent blinded reviewers analysed the MSCT. Results: 143 patients had previous stenting (232 stents) and 190 (82%) of the 232 stents were detected. Intrastent lumen was interpretable in 126 (64%) of the detected stents. Lumen interpretability depended on stent diameter: for stent diameter > 3 mm, 81% of lumens were interpretable, as against 51% with ⩽ 3 mm stent diameter (p < 0.001). Restenosis detection likewise depended on stent diameter: with small stents (⩽ 3 mm), sensitivity and specificity of MSCT were 54% and 100%, respectively; positive and negative predictive values were 100% and 94%. For stents with > 3 mm diameter, corresponding values were 86%, 100%, 100%, and 99%. Conclusion: 16 slice MSCT allows analysis of in-stent lumen in about half of all stented angioplasties. It performs better when stent diameter is more than 3 mm and may offer a non-invasive alternative to conventional coronary angiography for monitoring stented coronary arteries. Technical progress may improve interpretability and hence increase the yield of MSCT in this application.